High temperature thermopower of sol-gel processed Zn1-x-y Al (x) Me (y) O (Me: Ga, In) - DEMİRCİ, SELİM (SPRINGER, 2017)
In this study, dually doped samples of Zn1-x-y Al (x) Me (y) O (Me: Ga, In) were prepared by sol-gel process followed by hot isostatic pressing for high temperature thermoelectric applications. Material characterizations were performed with differential thermal analysis-thermogravimetry, Fourier transform infrared spectroscopy and X-ray diffraction on the target phases. Successful doping of the samples was confirmed by X-ray photoelectron spectroscopy and energy dispersive X-ray analysis. Thermopower values of the samples are found to be relatively high in analogy to semiconducting behavior in which negative values indicate electrons are the dominant charge carriers (n-type). Substitution of Zn2+ by Ga3+ and In3+ for Zn1-x-y Al (x) Me (y) O (Me: Ga, In) increases electron concentration in the samples and thereby decreases the thermopower values compared to Zn0.98Al0.02O. Considering the absolute values, In doped samples have higher thermopower (alpha (max) = -162 A mu V/K at 585 A degrees C for Zn0.96Al0.02In0.02O) compared to the Ga doped sample. Al and In dually doped Zn0.96Al0.02In0.02O could be considered as a promising n-type thermoelectric material for high temperature applications.
Keywords: THERMOELECTRIC TRANSPORT-PROPERTIES; DOPED ZNO